Novel cookies formula with Malva parviflora L. leaves powder as functional food: Evaluation of functional and technological properties - Nesren Elsayed; Bassem A. Sabry; Dina Mostafa Mohammed (Applied Food Research)
This study aimed to evaluate the protective effect of adding different concentrations of malva leaves powder (MLP) and assess the nutritional quality of cookies. The MLP had a potent content of protein, crude fiber, and ash. Additionally, eight fatty acids and seventeen phenolic compounds were identified. The antioxidant activity, total flavonoids, and total phenolic content of MLP were assessed. The quality characteristics of cookies, such as physical properties and sensory and antioxidant activity, were evaluated. The increased incorporation of malva leaves resulted in a progressive reduction in cookie samples' spread ratio and diameter. Color values of L* and b* of cookies samples incorporation with MLP were found in the range 66.47 to 47.84 and 25.24 to 14.34, respectively. The incorporation caused a greenish color in cookies at concentrations different from those in the control samples. Antioxidant analyses of cookies increased significantly with increasing the incorporation of MLP. The highest acceptance of cookies supplemented with MLP was noticed in 10 % of supplementation; meanwhile, the lowest acceptance in sensory evaluation was in 30 %. In conclusion, fortifying cookies with MLP. increased the bioactive compounds with acceptable impacts on their rheological and sensory attributes.